Evaluating the Efficacy of Cassava Flour and Tephrosia vogelii Mixture in Controlling Aphids in Kale - Charles Baida (Uganda Christian University, 2025)
Tephrosia vogelii and Cassava flour are natural and locally available potential alternative for pest control however little is known about the usage of T.vogelii and cassava flour in managing aphids in aphids. This research seeks to evaluate the efficacy of Tephrosia vogelii’s extract and cassava flour mixture in regulatory aphids in kale. The study used RCBD with 3 replications. The measured concentrations (0g, 70g, 140g and 210g) were assigned randomly. Data collected include counting the number of aphids before and after treatment, leaf damage, and the height of the plant, leaves among others. Results showed the key difference (<.001) among different mixture of T.vogelii and cassava flour in controlling aphids’ population on Kale. Where 0g was applied, highest number of live aphids of 18.09 ± 11.04a was recorded while the concentration (210g) had the lowest number of live aphids of 7.38 ± 7.99d. Highest leaf damage of 3.44±1.57a was observed in zero treatment (0g) while lowest damage was recorded in treatment (210g) of 1.87±0.83c. Kale treated with 210g of T.vogelii and cassava flour mixture had the highest aphid mortality rate of 4.66±5.15a while 0g had no mortality. The plant growth parameters with 0g had showed the lowest plant height of 11.58±4.97d while 210g had the highest plant height of 17.49±6.30a. The research findings have noted that 210g had insecticidal properties that were effective not just in killing aphids but also in reducing their impact on the kale plant.
Undergraduate